2017
DOI: 10.1140/epjb/e2017-70470-8
|View full text |Cite
|
Sign up to set email alerts
|

Finite-time synchronization of fractional-order simplest two-component chaotic oscillators

Abstract: Abstract. The problem of finite-time synchronization of fractional-order simplest two-component chaotic oscillators operating at high frequency and application to digital cryptography is addressed. After the investigation of numerical chaotic behavior in the system, an adaptive feedback controller is designed to achieve the finite-time synchronization of two oscillators, based on the Lyapunov function. This controller could find application in many other fractional-order chaotic circuits. Applying synchronized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…By comparing with analytical time of synchronization obtained above, it can be noted that syn ≤ 1 syn . This result respects the finite-time condition given in [42]. Thus, these results can be used for chaos based communications.…”
Section: Theorem 2 the Response System (10a)-(10c) Synchronizes Withsupporting
confidence: 78%
See 3 more Smart Citations
“…By comparing with analytical time of synchronization obtained above, it can be noted that syn ≤ 1 syn . This result respects the finite-time condition given in [42]. Thus, these results can be used for chaos based communications.…”
Section: Theorem 2 the Response System (10a)-(10c) Synchronizes Withsupporting
confidence: 78%
“…In [42], the authors have shown that the finite-time synchronization of fractional-order system is shorter than the finite-time synchronization of integer-order systems. This implies that the finite-time of synchronization for integerorder systems is also finite-time of synchronization for the fractional-order version of the same systems with the same controller involved.…”
Section: Theorem 2 the Response System (10a)-(10c) Synchronizes Withmentioning
confidence: 99%
See 2 more Smart Citations
“…A control Lyapunov function (CLF) scheme has also been reported for finite-time synchronization of chaotic systems (Wang, Han, Xie, & Zhang, 2009;Yu, 2010). The synchronization of uncertain fractional-order chaotic systems in finite-time has been studied by Li and Zhang (2016) and Kengne, Tchitnga, Mezatio, Fomethe, and Litak (2017). Abdurahman, Jiang, and Teng (2016) studied finite-time synchronization for a class of fuzzy neural networks with time-varying delays.…”
Section: Introductionmentioning
confidence: 99%